The Role of Brand Awareness as an Intervening Influence of Product Placement in the Drama "Today's Webtoon" on Interest in Buying Scarlett Whitening Products - Triwijayati, Anna; Nathania, Gladys Lugracia; Hellyani, Chatarina Aprilia (Asian Journal of Applied Business and Management, 2024)
This study aimed to analyze the effect of Scarlett Whitening's product placement in the drama "Today's Webtoon" on buying interest with brand awareness as an intervening variable. This research uses a quantitative method with explanatory research. The sampling procedure is non-probability sampling using purposive sampling technique. The study was conducted on 272 respondents who had watched the drama Today's Webtoon and used Scarlett Whitening products. This research uses primary data, and the survey collects data through Google Forms. The type of research analysis is the path analysis method. Hypotheses are tested using T-Test and Sobel Test. The results indicate that product placement has a positive and significant effect on purchase intention with brand awareness as the intervening variable.